Menakar Rekonsiliasi Laporan Keuangan Berbasis Web Pada KPU Provinsi Bali - Made Indrayani Santini; Ida Bagus Raka Suardana (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The purpose of this study are to determine the implementation of financial reporting reconciliation based on website application, which is e-Rekon LK G2, and to map the obstacles faced and the impact in implementing the reconciliation of financial statements based on e-Rekon LK G2 at KPU Provinsi Bali. The theory used in this research is the theory of public policy implementation by Van Meter and Van Horn. The indicators of the implementation of public policies used are Standards/Goals, communication, resources, disposition, bureaucratic structure, and socio-economic political environment. This study uses a qualitative descriptive method with data collection techniques using observation, interviews, and documentation. This study uses a qualitative descriptive method with data collection techniques using observation, interviews, and documentation. The results of the study indicate that there are several obstacles in the implementation of financial statement reconciliation based on e-Rekon LK G2 at KPU Provinsi Bali. These obstacles are regulatory changes, lack of detailed report printing features, inadequate data integration with State Property, data changes in the e-Rekon system take a long time, and Incoming Transfer Out Transfer transactions are vulnerable to difference.